(untitled) (Tzintzun, Revista de Estudios Históricos, 2021)
In this article we revisit the three main written sources on the great fire in Paracho Michoacán, occurred during the Mexican Revolution. We find that they present omissions and contradictions regarding the origins of the fire, the precise events of that day and what the dwellers did afterwards. Besides subjecting them to a critical analysis, we provide additional information stemming from bibliographical sources, archive documents and oral testimonies. It is the aim of this research to give a step forward towards tying some loose ends in the matter and to contribute to the enrichment of regional history regarding the last armed phase of the Mexican Revolution.